Managing State Finances Amid Globalization; Challenges And Opportunities - Fuad; Rio Rama Baskara (Fakultas Hukum Universitas Widya Mataram, 2024)
The increasing complexity and dependency of the global financial system are among the impacts of globalization on Indonesia's financial management. Globalization is often associated with the economy, politics, and society globally. This phenomenon indicates an increasing interconnectedness between countries worldwide. As a result, globalization creates broader impacts, influencing nearly every aspect of human life at the local, national, and global levels. The approach used in this study is qualitative with a literature review method. The results show that state financial management must be carried out in an orderly manner, in compliance with laws and regulations, and executed with high efficiency, economy, and effectiveness. Human resource competence becomes a critical element of achieving optimal state financial management. Globalization, a complex phenomenon involving economic, political, social, and cultural integration worldwide, is a process that accelerates interactions and exchanges between individuals, companies, governments, and institutions across different parts of the world. Globalization has become a significant factor influencing the regulation of state financial management. In the era of globalization, Indonesia faces unique challenges and opportunities in managing its finances. Some affected aspects include economic dependency due to Indonesia's increasing global connectivity through international trade, foreign investment, and capital flows. This affects state revenue and fiscal policy, as global economic fluctuations can impact tax revenue, commodity prices, and domestic financial market conditions. Keywords: challenges, finance, globalization. management, opportunities